Critical care nurses’ perception of causes and reported medication administration errors in government hospitals with specialists in Kelantan - Ishak, Muhammad Solehuddin (2023)
Introduction: Medication administration errors (MAEs) are a significant concern in critical care settings, posing risks to patient safety. Understanding the causes and factors associated with reported MAEs is crucial for developing effective prevention strategies. This study aimed to determine critical care nurses' perceptions of the causes and unreported of MAEs and identify factors significantly associated with reported MAEs in government hospitals with specialists in Kelantan. Methodology: This was a cross-sectional study using a validated questionnaire. It involved critical nurses from three government hospitals with specialists in Kelantan. The sample size was calculated based on the study objectives and the maximum number of samples required was 424. They were proportionately and randomly selected based on the size of the hospital and wards. The questionnaire consisted of a total of 64 questions, encompassing 28 items that investigated the causes of MAEs, 16 items that explored the reasons for the not reporting of MAEs, and 20 items that approximated the percentages of MAEs that were reported. The current study obtained approval from the institutional review board. Descriptive statistics and logistic regression were applied in the study. Results: A total of 424 critical care nurses participated voluntarily. Their mean age was 40.90 (6.13) years and their mean working duration was 16.83 (5.90) years. The majority perceived that the primary cause of MAEs was illegibility of physician's medication order and the main reason for not reporting MAEs because the administration focuses on the individual rather than the system when medication errors occur. The study also revealed significant factors such as nurses working in HDW (AOR = 4.87, 95% CI: 1.58, 15.02), who had personal experience with (AOR = 2.09, 95% CI: 1.11, 3.92) and had seen MAEs (AOR = 1.91, 95% CI: 1.19, 3.07) were more likely to report the incident. Conclusion: The current study found that critical care nurses perceived that working in the HDW, and having experienced or seen MAEs were factors associated with reporting MAEs. Enhancing patient safety culture may encourage error reporting and mitigate MAE. Government hospitals should allow nurses to report problems anonymously. Rather than individual blame, a non-punitive approach and system development may increase reporting rates.